The five gradients inequality for non quadratic costs - Caillet, Thibault (Comptes Rendus. Mathématique)
We give a proof of the “five gradients inequality” of Optimal Transportation Theory for general costs of the form $c(x,y)=h(x-y)$ where $h$ is a $C^1$ strictly convex radially symmetric function.